ERROR ANALYSIS OF WRITTEN PEER FEEDBACK ON STUDENTS’ WRITING TASK AT PONDOK PESANTREN DARUL HADIST AIR RIAU KINALI - Fauziah Putri; Hilma Pami Putri (Institut Agama Islam Negeri (IAIN) Bone, 2022)
The background of the research was the problems faced by students in providing feedback on students’ writing in the 11th grade of Madrasah Aliyah (MA) Pondok Pesantren Darul Hadist Air Rau Kinali. There were some problems that the researcher found. First one, some students did some error in correcting their peers because their English is limited. The last one, the students didn’t learn from the error because the teacher didn’t discuss the error with the students. The purpose of this research was to find out what types of errors were made in a written peer feedback that was used by the eleventh grades students of Madrasah Aliyah (MA) Pondok Pesantren Darul Hadist Air Rau Kinali. In this research, the researcher used a qualitative descriptive research. The researcher took total sampling to take the data. There were 18 students in Madrasah Aliyah (MA) that applied peer feedback in writing. The data was obtained through the students’ writing tasks, namely writing descriptive text. Analyzed the writing task based on the theory from Ellis. From the results of the research, the type of errors that mostly the peers made was misformation. This is because many students make errors in tobe and personal pronouns. After misformation the error made by the peers was omission, then come to misordering, and the last error of addition.